Chemically Robust Phthalocyanines: Photosensitizer and Electron Shuttle in Solid State Dye Sensitized Solar Cells. Issue 1784 (11th June 2015) - Dwyer, Patrick J.; Vander Valk, Rory J.; Kelty, Stephen P.
ABSTRACT: A completely solid state dye sensitized solar cell (DSSSC) is proposed in which chemically robust phthalocyanine (Pc) sensitizers, F16 ZnPc and F40 ZnPc, are sandwiched between n-TiO2 and p-NiO. While the energy conversion efficiencies of conventional Grätzel cells are continually increasing, the DSSSC design effectively solves the long term stability issues of the volatile liquid electrolyte. Through analysis of the electronic structure of the Pc|semiconductor systems, the free energy associated with hole injection into the valence band of NiO upon photoexcitation of the sensitizer and electron injection into the conduction band of TiO2 from the reduced form of the sensitizer as well as the competing charge recombination processes are calculated. Thermodynamically, the charge injection processes are found to be favored over the undesired charge recombination processes. These findings suggest promising energy conversion for the NiO|Pc|TiO2 DSSSC.